One Pot, Four Component Synthesis of Phthalazine-1,4-diones Derivatives in [BMIM][OH] Medium - Loka Maheshwari, D.P.; Satyanarayana, B. (Asian Journal of Chemistry, 2019)
[BMIM][OH] mediated, green and efficient synthesis of phthalazines (5) have been developed by condensing diethyl phthalate (1), ethyl cyanohydrazide (2), substituted benzaldehyde (3) and malononitrile (4) in the presence of Meldrum’s acid at 60-65 °C and at room temperature for 60-90 min. The importance of this method includes shorter reaction time and high yield.